1981
DOI: 10.1042/bj1990239
|View full text |Cite
|
Sign up to set email alerts
|

The effect of limited proteolysis on rabbit muscle creatine kinase

Abstract: Creatine kinase from rabbit muscle is inactivated by limited proteolysis with proteinase K from Tritirachium album. Gel-filtration and cross-linking studies showed that the limited proteolysis did not affect the molecular weight of the enzyme under non-denaturing conditions, but did cause changes in the reactivity of the reactive thiol group on each subunit and in the ability of the enzyme to form a 'transition-state analogue' complex in the presence of magnesium acetate plus ADP plus creatinine plus NaNO3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
(27 reference statements)
2
14
0
Order By: Relevance
“…Experiments involving cross-linking of the proteolysed enzyme have shown that, under non-denaturing conditions, the small and large fragments remain associated (Price et al, 1981). When the fragments are separated by treatment with denaturing agents such as guanidine hydrochloride, the ability to refold on dilution of the denaturing agent is greatly impaired.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments involving cross-linking of the proteolysed enzyme have shown that, under non-denaturing conditions, the small and large fragments remain associated (Price et al, 1981). When the fragments are separated by treatment with denaturing agents such as guanidine hydrochloride, the ability to refold on dilution of the denaturing agent is greatly impaired.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with an equilibrium unfolding study of proteinse K‐nicked MM‐CK. Although native MM‐CK is digested with proteinase K at a unique site in a large surface loop between strands β9 and β10, the fragments remain associated below 0.9 M GdmCl 4, 36–38…”
Section: Resultsmentioning
confidence: 70%
“…We also need to explain why the two peptides remain firmly associated after proteinase K treatment, requiring urea or SDS treatment to dissociate them (Price et al, 1981). Since there are no disulphide bridges in CK (Watts, 1973), such a strong interaction is likely to be hydrophobic.…”
Section: Monoclonal-antibody Studies Of Creatine Kinasementioning
confidence: 99%